Post–Endoscopic Retrograde Cholangiopancreaticography complications in liver transplanted patients, a single-center experience. (June 2015) - Ambrus, R. B.; Svendsen, L. B.; Hillingsø, J. G.; Hansen, M. L.; Achiam, M. P.
Background: Complications in the biliary tract occur in 5%−30% after liver transplantation and the main part of the complications is successfully managed with endoscopic retrograde cholangiopancreaticography (ERCP). The incidence and risk factors for post-ERCP complications in liver transplantation patients are not well described. Our objective was to define the frequency of post-ERCP complications in liver transplantation patients at the Abdominal Center, Rigshospitalet, the only Liver Transplantation Center in Denmark. Methods: Retrospective study of all ERCPs performed in liver transplantation patients during a 9-year period. Results: A total of 292 ERCPs were included. Overall post-ERCP complications occurred in 24 procedures (8.2%): pancreatitis in 8 (2.7%), bleeding in 5 (1.7%), and cholangitis in 13 (4.5%) procedures. Simultaneous pancreatitis and cholangitis, and simultaneous bleeding and cholangitis occurred after two procedures, respectively. Multivariate analysis concerning overall complications identified biliary sphincterotomy ( p = 0.006) and time since liver transplantation within 90 days postoperatively ( p = 0.044) as risk factors for post-ERCP complications. Specifically concerning post-ERCP pancreatitis (PEP), it was found that pre-ERCP cholangitis was another independent risk factor for PEP ( p = 0.026). Stent in the biliary tract prior to ERCP seemed to be protective ( p = 0.041). Conclusions: Complications were of surprisingly mild degree. The rates of post-ERCP complications in our study were in line with previous studies with liver transplantation patients. Cholangitis prior to ERCP may be another risk factor for post-ERCP pancreatitis.